Use of Pharmacogenetic Drugs by the Dutch Population - Alshabeeb, Mohammad A.; Deneer, Vera H. M.; Khan, Amjad; Asselbergs, Folkert W. (Frontiers in Genetics, 2019)
Introduction: The Dutch Pharmacogenetics Working Group (DPWG) indicated a list of actionable genotypes that affect patients’ response to more 50 drugs; these drugs which show variable effects based on patients’ genetic traits were named as pharmacogenetics (PGX) drugs. Preemptive genetic testing before using these drugs may protect certain patients from serious adverse reactions and could help in avoiding treatment failures. The objectives of this study include identifying the rate of PGX drug usage among Dutch population, estimating the level of users who carry the actionable genotypes and determining the main genes involved in drug’s effect variability. Method: Usage of PGX drugs over 2011-2017 by the insured population (an average of 11.4 million) in outpatient clinics in the Netherlands was obtained from the publically available GIP databank. The data of 45 drugs were analysed and their interactions with selected pharmacogenes were estimated. Frequency of actionable genotypes of 249 Dutch parents was obtained from the public database: Genome of the Netherlands (GONL), to identify the pattern of genetic characteristics of Dutch population. Results: Over a seven year period, 51.3 million exposures of patients to PGX drugs were reported with an average of 5.3 exposures per each drug user. One quarterof the exposures (12.4 million) are predicted to be experienced by individuals with actionable genotypes (risky exposures). Up to 60 % of the risky exposures (around 7.5 million) were related to drugs metabolised by CYP2D6. SLCO1B1 and CYP2C19 were also identified among the top genes affecting response of drugs users (involved in about 22% and 12.4% of the risky exposures, respectively). Cardiovascular medications were the top prescribed PGX drug class (43%), followed by gastroenterology (29%) and psychiatry/neurology medications (15%). Women use more PGX drugs than men (55.8% versus 44.2%, respectively) with the majority (84%) of users in both sexes are above 45 years. Conclusion: PGX drugs are commonly used in the Netherlands. Preemptive panel testing for CYP2D6, SLCO1B1 and CYP2C19 only could be useful to predict 95% of vulnerable patients’ exposures to PGX drugs. Future studies to assess the economic impact of preeemtive panel testing on patients of older age are suggested.